2021
DOI: 10.1002/osp4.516
|View full text |Cite
|
Sign up to set email alerts
|

Measuring ketone bodies for the monitoring of pathologic and therapeutic ketosis

Abstract: Background The ketone bodies β‐hydroxybutyrate (BOHB) and acetone are generated as a byproduct of the fat metabolism process. In healthy individuals, ketone body levels are ∼0.1 mM for BOHB and ∼1 part per million for breath acetone (BrAce). These levels can increase dramatically as a consequence of a disease process or when used therapeutically for disease treatment. For example, increased ketone body concentration during weight loss is an indication of elevated fat metabolism. Ketone body measurement is rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 115 publications
2
18
0
1
Order By: Relevance
“…Seventy-five percent of control-diet-fed mice were detected with more than 250 erythrocytes/microliter in urine, whereas only 14.3% (1/7) of kawain-diet-fed male mice were found with more than 250 erythrocytes/microliter at the age of 23 weeks ( Figure 3 C,D). The majority of kawain-diet-fed mice were detected with ketone body in their urine, but this was absent in urine from control-diet-fed mice, suggesting that the kawain diet may have effects on fat catabolism in the UPII mutant Ha-ras model [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seventy-five percent of control-diet-fed mice were detected with more than 250 erythrocytes/microliter in urine, whereas only 14.3% (1/7) of kawain-diet-fed male mice were found with more than 250 erythrocytes/microliter at the age of 23 weeks ( Figure 3 C,D). The majority of kawain-diet-fed mice were detected with ketone body in their urine, but this was absent in urine from control-diet-fed mice, suggesting that the kawain diet may have effects on fat catabolism in the UPII mutant Ha-ras model [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is especially relevant for ketoacidosis management when device accuracy is fundamental for a patient’s well-being. Further studies are needed to clarify the relationship between breath acetone testing and dynamics during ketoacidosis (also see Anderson et al, 2021 [ 10 ]). Informed by this research, device engineers and designers will be able to develop user-friendly prototypes for performance testing in various clinical scenarios in which ketone testing is relevant in diabetes care (e.g., sick day management of T1DM, DKA diagnosis by school nurses, general practitioners, ambulance officers and emergency department staff, monitoring for DKA in type 2 diabetes and potentially T1DM users of sodium glucose transporter type 2 inhibitors).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found a significant relationship between the blood ketone body β-hydroxybutyrate and breath acetone exhaled during respiration in adults [ 7 11 ], and to some extent in young people [ 12 , 13 ], including responses to ketogenic diets and during episodes of DKA. Thus, the measurement of the breath acetone concentration provides a non-invasive method to measure the level of ketosis [ 8 ] ( Table 1 ), and if developed and validated for use in T1DM could help in prevention of severe DKA through early detection [ 10 ]. Non-invasive technologies are of particular interest for young patient groups, with studies reporting more fear and pain related to finger pricking and injections among younger children [ 14 , 15 ] and adolescents [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…KB become the primary energy source by cells with mitochondria and, most importantly, by the brain. This significant rise in KB in course of KD it is known as “nutritional ketosis” ( 17 ), a condition in which plasma KB concentration physiologically increases (at least > 0.5 mM ( 18 )), resulting in a rather safe nutritional approach ( 19 ).…”
Section: Definition and Types Of Ketogenic Dietsmentioning
confidence: 99%